Trajectories of declining and destructive capitalism - Herrera, Rémy (Emerald Publishing Limited, 2025)
Spanning three parts, Volume 40 of Research in Political Economy explores themes related to various "trajectories of declining and destructive capitalism" within the framework of contemporary Marxism. Social scientists from ten countries at various stages of their careers work to strengthen Marxism, applying its methods to the interpretation and, above all, the transformation of the world. The chapters cover five continents and thirteen countries: Germany, Great Britain, France, Spain, Senegal, South Africa, Lebanon, Iran, India, Papua New Guinea, and Chile in the current period or very near past - plus two other countries, China and Cuba, in their more distant past preceding their respective socialist revolutions. Providing a far-reaching and comprehensive overview of the damaging impact of capitalism across the globe, Trajectories of Declining and Destructive Capitalism confronts economic strategies at a pivotal moment in international politics.
Keywords: Capitalism -- History -- 20th century.; Business & Economics -- Economics -- Theory.; Far-left political ideologies and movements.; Economic theory and philosophy.; elektronické knihy; electronic books